Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

A root of x2 – 5x – 1 = 0 is

Sagot :

luana
[tex]x^2-5x-1=0\\\\ a=1,\ b=-5,\ c=-1\\\\ \Delta=b^2-4ac=(-5)^2-4*1*(-1)=25+4=29\\\\ \sqrt{\Delta}=\sqrt{29}\\\\ x_1=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-\sqrt{29}}{2*1}=\frac{5-\sqrt{29}}{2}\\\\ x_2=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+\sqrt{29}}{2*1}=\frac{5+\sqrt{29}}{2}\\ [/tex]
Louli

Answer:

The roots are [tex] \frac{5+\sqrt{29}}{2} [/tex] and [tex] \frac{5-\sqrt{29}}{2} [/tex]

Explanation:

The general form of the quadratic equation is:

ax² + bx + c = 0

The given equation is:

x² - 5x - 1 = 0

By comparison:

a = 1

b = -5

c = -1

To get the roots of the equation, we will use the quadratic formula shown in the attached image.

This means that:

either [tex] x = \frac{5+\sqrt{(-5)^2-4(1)(-1)}}{2(1)} = \frac{5+\sqrt{29}}{2} [/tex]

or [tex] x = \frac{5-\sqrt{(-5)^2-4(1)(-1)}}{2(1)} = \frac{5-\sqrt{29}}{2} [/tex]

Hope this helps :)

View image Louli
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.